The Influence of Emotional Marketing and Sharia Marketing on Consumer Decisions in Purchasing Waqf Policy Insurance Products (Case Study at PT Asuransi Syariah Keluarga Indonesia) - Marsela, Indri; Devi, Abrista; Hakim, Nurman (Tazkia Islamic Finance and Business Review, 2023)
Abstract. The development of sharia economics and finance has experienced significant developments in recent years. This is marked by several main developments in the financial sector and sharia financial instruments, which are increasingly varied and diversifying to meet the diverse needs of the public or customers. One of the sharia financial institutions that is experiencing development is sharia insurance. The sharia insurance industry has become an integral part of modern society's lives. In the midst of the various choices of sharia insurance products, innovation in sharia insurance products combined with waqf instruments is one of the good things for the expansion of sharia financial instruments. Companies marketing waqf insurance policies face increasingly complex challenges to understand, reach, and win the hearts of consumers. The decision to purchase a waqf policy insurance product no longer only revolves around financial considerations but also includes emotional dimensions and deep religious values. This research aims to determine the influence of emotional marketing and sharia marketing on consumer decisions in purchasing policy waqf insurance products using the method used by researchers, namely associative research with a quantitative approach. This research used a sample of 40 respondents with 19 questionnaire statements. In this study, the model used uses a linear regression model involving more than one independent variable or predictor (multiple linear regression). This research shows that, partially or simultaneously, the emotional marketing and sharia marketing variables are stated to have a significant influence on consumer decisions in purchasing waqf insurance policies. This is obtained from the coefficient of determination value in the very strong category, which is between 0.80 and 1,000, with an adjusted R square result of 0.818, or around 81.8%, influencing consumer decisions and the remaining 18.2% being influenced by other variables outside of this research. Keywords: Emotional Marketing, Sharia Marketing, Consumer Decisions, Waqf Insurance Policies.